Doing business in a digital world - Hausman, Angela (Journal of business & industrial marketing, 2005)
This e-book offers a multi-national perspective on factors relating to digital technologies in business-to-business markets. Comprising ten articles in all it features the work of leading authors such as George, S. Day, S. Tamer Cavusgil, Roger J. Calantone and Robert E. Spekman. The first group of articles deals with utilization of information technology by firms as both a marketing tool and a means to manage supply chains effectively. The second group deals with different digital technologies and explores how these have been used to improve firm effectiveness. In sum, the articles provide bo.